(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Robotic surgery and artificial intelligence are transforming modern surgery by enhancing precision, minimizing invasiveness, and supporting clinical decision-making. This narrative review, based on 40 studies published between 2020 and 2025, explores their applications, benefits, and challenges. Robotic surgery improves ergonomics and reduces complications and hospital stays, though it often involves longer procedures and higher costs. Artificial intelligence supports all surgical stages through predictive modeling, image guidance, and performance evaluation. Despite ongoing issues with algorithm transparency, data quality, and ethics, both technologies show great potential to advance surgical care toward safer, more efficient, and personalized medicine.